A method of assessment during vocational training: report of a pilot study - Stanley, I.M. (1985)
Problems arising from the present rate of failure of vocational trainees in the MRCGP examination are outlined; and the role of formative assessment during training in reducing this rate is considered. A study is described in which trainees in a number of centres were assessed by a method designed to measure specified cognitive abilities and areas of knowledge. The method, based on written papers, provides each candidate with a profile of performance and generates comparative standards. Reliability of marking, the distribution of candidate-scores within and between areas of assessment and techniques for monitoring the effectiveness of questions are reported. Use of the method by College as an educational service to trainees is considered, along with its potential as a Part I MRCGP examination.